Electronic-temperature estimation of Joule-heated graphene via Raman investigations - Seo, Minky; Kim, Do Hoon; Lee, Jae Hyun; Son, Seok Kyun (Journal of the Korean Physical Society, 2021)
Temperature-dependent Raman scattering provides valuable information on electron–phonon coupling and phonon anharmonicity of graphene. In this study, we show an enhancement of Joule heating in graphene by confining the current flow in a narrow channel. In addition, we performed a detailed analysis of the anharmonic effect in the hBN/monolayer graphene/hBN heterostructure based on the behaviour of the full-width at half maximum of the G mode with increasing electric power: a non-monotonic trend, leading to the key of approximation of the electronic temperature in graphene. We believe our results could offer a convenient analysis tool to study electron–phonon coupling and anharmonic phonon-decay processes in a high-temperature regime.
Keywords: Electron temperature; Graphene; Hot phonons; Joule heating; Raman spectroscopy